2012
DOI: 10.1136/bmjopen-2011-000595
|View full text |Cite
|
Sign up to set email alerts
|

An ecological study on the geographic patterns of ischaemic heart disease in Portugal and its association with demography, economic factors and health resources distribution

Abstract: ObjectivesBeing one of the main causes of morbidity and mortality in developed countries, ischaemic heart disease's (IHD) incidence and mortality present clear differences between and within countries. Several authors already proposed possible explanations based on the demography, environmental factors, diet and level of urbanisation. This study reflects the Portuguese reality concerning IHD, by analysing the geographical distribution of hospital admissions and mortality due to this condition, in Portugal, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…[20][21][22][23] Nevertheless, the strong regional differences in diseases, such as coronary heart disease, remain partially unexplained, possibly due to the restricted diversity (mostly economic and health resources) of the explanatory variables that have been considered. 20 On the basis of the research from the UK and NZ, we aimed to develop a Portuguese measure of multiple environmental deprivation (PT-MEDIx). Our aim was also to assess how the choice of the environmental factors, datasets and methods of analysis should be adapted to the Portuguese idiosyncrasies without compromising comparability.…”
mentioning
confidence: 99%
“…[20][21][22][23] Nevertheless, the strong regional differences in diseases, such as coronary heart disease, remain partially unexplained, possibly due to the restricted diversity (mostly economic and health resources) of the explanatory variables that have been considered. 20 On the basis of the research from the UK and NZ, we aimed to develop a Portuguese measure of multiple environmental deprivation (PT-MEDIx). Our aim was also to assess how the choice of the environmental factors, datasets and methods of analysis should be adapted to the Portuguese idiosyncrasies without compromising comparability.…”
mentioning
confidence: 99%
“…Understandably then, agencies such as the World Health Organization and policy initiatives like Healthy People 2020 now acknowledge that health is too complex a phenomenon to not be considered within the broader social, cultural, and economic environments in which people live, work, and play (Evans, Barer, & Marmor, 1994;Marmot, 2005;Solar & Irwin, 2010). Thus, the emergent trend is to examine how and to what extent the various psychosocial, economic and political, and biological pathways of social determinants of health synergistically influence health, both positively and adversely (Chin et al, 2012;Chin, Walters, Cook, & Huang, 2007;Colditz & Wei, 2012;Cummins, Stafford, Macintyre, Marmot, & Ellaway, 2005;Ferreira-Pinto LM, 2012;Ferrie, Martikainen, Shipley, & Marmot, 2005;Freudenberg, Klitzman, & Saegert, 2009;Gerend & Pai, 2008;Knutson, 2012;Kumari, Marmot, Rumley, & Lowe, 2005;Solar & Irwin, 2010;Vona-Davis & Rose, 2009).…”
Section: Reducing Infant Mortality Health Disparitiesmentioning
confidence: 99%
“…This report states that it is difficult to assess and monitor the extent of the health inequalities in Portugal, due to the lack of a monitoring system of health indicators by target population groups, owing, at least in part, to a narrow interpretation of the data confidentiality law. A recent ecological study showed geographic variation in hospital admissions and in-hospital mortality of patients admitted with ischemic heart disease in Portugal from 2000 to 2007, with the interior regions showing higher rates, not fully explained by socio-demographic, economical and health resource factors [9]. It is of interest to expand this observation to a longer period and to consider total mortality, in addition to in-hospital mortality.…”
Section: Introductionmentioning
confidence: 99%